Malstil und Schreibsprache Kunsthistorisch-stilkritische und sprachwissenschaftliche Untersuchungen zur Lokalisierung des Münchener "Jüngeren Titurel" (München, Bayerische Staatsbibliothek, Cgm 8470) - Roland, Martin (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
Interdisciplinary cooperation enables the two authors to precicly localize and date one of the most lavishly produced manuscript of a medieval German epic during 15th century. With the combination of art-historical and linguistic methods the "Münchener Jüngere Titurel" (BSB, Cgm 8470) - hithero beliefed to be of Tyrolian or Vienese origin - was dated (c. 1430/35) and localised (Regensburg). The exemplary study proves the potential of cooperations within the humanities.